2016
DOI: 10.1371/journal.pone.0164537
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Critically Ill Patients with Cancer-Related Complications

Abstract: IntroductionCancer patients are at risk for severe complications related to the underlying malignancy or its treatment and, therefore, usually require admission to intensive care units (ICU). Here, we evaluated the clinical characteristics and outcomes in this subgroup of patients.Materials and MethodsSecondary analysis of two prospective cohorts of cancer patients admitted to ICUs. We used multivariable logistic regression to identify variables associated with hospital mortality.ResultsOut of 2,028 patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 49 publications
1
19
1
5
Order By: Relevance
“…Despite the fact that patients with metastatic cancer had an indication for being admitted into the intensive care units, it was not so because of their predicted poor prognosis[ 13 ]. The development of new oncology therapies has improved survival in cancer patients, and therefore, increased the probability of developing medical complications requiring admission to the ICU, such as intestinal obstruction, infections, respiratory failure, acute kidney injury, among others, and complications associated with cancer treatment[ 14 ]. It has been proven that patients with even advanced stage of cancer who have control over their disease through oncological treatment, i.e ., having stable disease or partial/complete response as well as acute medical morbidities have a similar prognosis as patients without cancer and admitted to the ICU[ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that patients with metastatic cancer had an indication for being admitted into the intensive care units, it was not so because of their predicted poor prognosis[ 13 ]. The development of new oncology therapies has improved survival in cancer patients, and therefore, increased the probability of developing medical complications requiring admission to the ICU, such as intestinal obstruction, infections, respiratory failure, acute kidney injury, among others, and complications associated with cancer treatment[ 14 ]. It has been proven that patients with even advanced stage of cancer who have control over their disease through oncological treatment, i.e ., having stable disease or partial/complete response as well as acute medical morbidities have a similar prognosis as patients without cancer and admitted to the ICU[ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a literature review of adult patients with solid cancers admitted to the ICU from January 2000 to April 2014, Puxty et al [4] identified 48 studies, among which in-ICU mortality was reported in 32 studies, in-hospital mortality reported in 25 studies, and mortality at 1, 3, and 6 months, respectively, reported in only 4, 5, and 7 studies. One of the most obvious reasons is that studies on cancer patients hospitalized in the ICU are still ongoing, and even the most recent ones continue to mix patients with hematological malignancies and those with solid cancers under the generic term “cancer patients” [5, 6]. However, there is evidence for several years that the prognosis of solid cancer patients is totally different depending on the type of cancer, whether hematological or solid [7].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most frequently encountered complications in critically ill cancer patients is RF[ 6 ]. In cancer patients with RF who require ventilator support, endotracheal intubation with invasive mechanical ventilation (IMV) is the most common treatment modality[ 7 ].…”
Section: Introductionmentioning
confidence: 99%